2021
DOI: 10.1080/10489223.2021.1934685
|View full text |Cite
|
Sign up to set email alerts
|

Learning embedded verb placement in Norwegian: Evidence for early overgeneralization

Abstract: This article investigates how children acquire word order generalizations from ambiguous and infrequent input. We focus on verb placement in Norwegian relative and complement clauses. In two elicitation experiments we explore where children (age 3-7) place verbs in three embedded clauses types: one requiring a purely syntactic generalization and two requiring a semantic-pragmatic generalization. We find that children overgeneralize the main clause word order to embedded clauses. However, this happens with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…It should be noted that the word order in Norwegian subordinate clauses is superficially identical to main clause word order when the subordinate clause does not contain adverbials. Thus, it has been suggested that children in their initial stages of language acquisition assume that the verb placement in main clauses may be extended to subordinate clauses (Ribu et al, 2019;Ringstad & Kush, 2021;Westergaard & Bentzen 2007, p. 282).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the word order in Norwegian subordinate clauses is superficially identical to main clause word order when the subordinate clause does not contain adverbials. Thus, it has been suggested that children in their initial stages of language acquisition assume that the verb placement in main clauses may be extended to subordinate clauses (Ribu et al, 2019;Ringstad & Kush, 2021;Westergaard & Bentzen 2007, p. 282).…”
Section: Discussionmentioning
confidence: 99%
“…In Norwegian, relative clauses emerge early in the production of TD children (Ribu, Simonsen, Løver, Strand & Kristoffersen, 2019). However, their internal word order causes problems, because the sentence adverbial in subordinate clauses is placed in front of the verb rather than after the verb as in main clauses (Ringstad & Kush, 2021;Westergaard & Bentzen, 2007). As we will discuss in more detail below, Norwegianspeaking children tend to overgeneralize the main clause word order when they start using relative clauses.…”
Section: Syntax In Children With Developmental Language Disordermentioning
confidence: 99%
See 1 more Smart Citation